Peluang Bisnis Menjadi Konten Kreator Di Kalangan Remaja Milenial Pada Era Digital Desa Banjar Kemuning Sedati Sidoarjo - Suyono Suyono; Suhari Suhari; Dwi Retnani Srinarwati; Bernadetta Budi Lestari; Aldi Wahyu Saputra; Abil Wafa Almaulana; Melania Tesa Iana Maya Anugraheni (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Content creators appear in various digital media with a variety of works either writing, images, videos, or two combinations of material. In the digital era, which is inseparable from social media among teenagers, it provides a great opportunity for content creators to be creative by making it a business field. The purpose of community service is to motivate teenagers in Banjar Kemuning Village to create business opportunities as content creators. Methods used with lectures. The result of community service is that the training of creator business opportunities among millennial teenagers provides a way to earn income by becoming content creators on social media.